Polyurethane foam
By increasing the biomass content of polyurethane foam to more than 24%, the problem of poor drying after washing is solved, and a faster and more thorough drying effect is achieved.
Patent Information
- Application Number
- CN202411652505.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-18
- Publication Date
- 2025-03-14
AI Technical Summary
Due to its small bubble structure, polyurethane foam has problems such as high water retention and poor drying after washing.
By increasing the biomass content, the specific method is to measure the biomass content by accelerator mass spectrometry (AMS method) according to the ASTM D6866-20 standard to ensure that it reaches more than 24%, thereby improving the dryness after washing.
The drying properties of polyurethane foam after washing are improved, and the drying time is shortened, so that the product can dry faster and more thoroughly after washing.
Smart Images

Figure CN119613650A_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese invention patent application with the application date of October 18, 2021, application number 202180103415.X, and name “Polyurethane Foam”. Technical Field
[0002] An object of the present invention is to provide a polyurethane foam having good drying properties after washing. Background Art
[0003] Polyurethane foam is formed from a polyurethane foam composition containing a polyol component, an isocyanate, and a foaming agent, and is widely used as bedding, clothing, and the like (Patent Documents 1, 2, and 3).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2005-270146
[0007] Patent Document 2: Japanese Patent Application Publication No. 2019-17948
[0008] Patent Document 3: Japanese Patent Application Publication No. 2019-203061 Summary of the Invention
[0009] Problems to be solved by the invention
[0010] However, polyurethane foam has a problem of high water retention and poor drying properties after washing because it is composed of a fine cell (cell) structure.
[0011] An object of the present invention is to provide a polyurethane foam having good drying properties after washing.
[0012] Means of solving problems
[0013] The present invention is characterized by a polyurethane foam having a biomass content of 24% or greater as measured according to ASTM D6866-20.
[0014] Effects of the Invention
[0015] The polyurethane foam of the present invention has a biomass content of 24% or more as measured in accordance with ASTM D6866-20, whereby drying properties after washing become good.
[0016] Biomass content refers to the proportion of natural raw materials contained in a product. The biomass content of a product can be measured by measuring how much radioactive carbon C14, which only exists in naturally derived materials, is contained in the product.
[0017] The biomass content in the present invention is obtained by measuring the C14 concentration of the polyurethane foam by accelerator mass spectrometry (AMS method) based on ASTM D6866-20 and calculating the ratio (%) of the C14 concentration relative to 100% natural origin materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a table showing the formulations, physical properties, and post-wash drying properties of each Example and each Comparative Example of the present invention.
[0019] Figure 2 This is a table showing the contents of each program of the detergency test.
[0020] Figure 3 This is a table showing the results of the drying test. DETAILED DESCRIPTION
[0021] Since the polyurethane foam of the present invention has a biomass content of 24% or more as measured by accelerator mass spectrometry (AMS method) in accordance with ASTM D6866-20, drying properties after washing are improved, and drying time can be shortened.
[0022] Polyurethane foams come in various types, including rigid, semi-rigid, and flexible, and can be selected based on the intended use. For example, flexible polyurethane foams are widely used in bedding such as mattresses and clothing such as bra pads for underwear. The polyurethane foam of the present invention can include any of rigid, semi-rigid, and flexible polyurethane foams.
[0023] The polyurethane foam of the present invention can be obtained from a polyurethane foam composition containing a polyol component, a polyisocyanate and a blowing agent. The polyurethane foam composition is mixed and stirred to react with the polyol component and the polyisocyanate, and foam to form the polyurethane foam.
[0024] The polyol component contains a polyol, which is a compound having two or more hydroxyl groups per molecule. The polyol component contains a plant-derived polyol. Plant-derived polyols are polyols produced using plant-derived raw materials such as vegetable oils.
[0025] Examples of vegetable oils include castor oil, sunflower oil, rapeseed oil, linseed oil, cottonseed oil, tung oil, coconut oil, poppy seed oil, corn oil, and soybean oil. Among them, castor oil polyol produced from castor oil is a preferred example of a plant-derived polyol.
[0026] The castor oil polyol may be either modified castor oil polyol or unmodified castor oil polyol, or may contain both.
[0027] Examples of modified castor oil polyols include transesterification products of castor oil and fats other than castor oil, transesterification products of castor oil and fat fatty acids, transesterification products of castor oil and polyols, esterification products of castor oil fatty acids and polyols, esterification products of a part of the hydroxyl groups contained in castor oil and monocarboxylic acids such as acetic acid, products obtained by addition polymerization of alkylene oxides to the above chemical substances, and hydrogenated products obtained by addition of hydrogen to the above chemical substances.
[0028] Examples of the unmodified castor oil polyol include purified castor oil polyol, semi-refined castor oil polyol, and unrefined castor oil polyol.
[0029] The number of functional groups of the plant-derived polyol is preferably 2 to 3.5, the hydroxyl value is preferably 40 to 180 mgKOH / g, and the molecular weight is preferably 724 to 2931, and one or more kinds of the plant-derived polyol may be used.
[0030] The amount of plant-derived polyol is determined so that the biomass content, as measured according to ASTM D6866-20, is 24% or greater. However, it is preferably 15 parts by mass or greater, more preferably 30 parts by mass or greater, and even more preferably 80 parts by mass or greater, per 100 parts by mass of the polyol component. The polyol component may also contain a petroleum-derived polyol. The inclusion of a petroleum-derived polyol improves moldability and productivity.
[0031] The petroleum-derived polyol may be any one of polyether polyol, polyester polyol, polyetherester polyol, etc., or one or more of them may be used.
[0032] Examples of the polyether polyol include polyether polyols obtained by adding alkylene oxides such as ethylene oxide and propylene oxide to polyols such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, butylene glycol, neopentyl glycol, glycerin, pentaerythritol, trimethylolpropane, sorbitol, and sucrose.
[0033] Examples of the polyester polyol include polyester polyols obtained by polycondensation of an aliphatic carboxylic acid or an aromatic carboxylic acid with an aliphatic diol, wherein the aliphatic carboxylic acid is malonic acid, succinic acid, adipic acid, etc., the aromatic carboxylic acid is phthalic acid, etc., and the aliphatic diol is ethylene glycol, diethylene glycol, propylene glycol, etc.
[0034] Examples of the polyetherester polyol include a polyol obtained by polyesterification by reacting a polyether polyol with a polybasic acid, and a polyol having two segments of a polyether and a polyester in one molecule.
[0035] The petroleum-derived polyol preferably has a functional group number of 2.0 to 3.5, a hydroxyl value of 15 to 1000 mgKOH / g, and a molecular weight of 100 to 10,000.
[0036] The polyisocyanate is not particularly limited and may be any of aromatic, alicyclic, and aliphatic types. It may also be a bifunctional isocyanate having two isocyanate groups in one molecule, or a trifunctional or higher functional isocyanate having three or more isocyanate groups in one molecule. These may be used alone or in combination.
[0037] Examples of bifunctional polyisocyanates include 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 2,2'-diphenylmethane diisocyanate (2,2'-MDI), xylene diisocyanate, and 3,3 Aromatic substances such as 4,4'-dimethylbiphenyl diisocyanate and 3,3'-dimethoxy-4,4'-biphenyl diisocyanate; alicyclic bifunctional polyisocyanates such as cyclohexane-1,4-diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, and methylcyclohexane diisocyanate; and aromatic bifunctional polyisocyanates such as butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropyl diisocyanate (isopropylene diisocyanate), methylene diisocyanate, and lysine diisocyanate. It should be noted that diphenylmethane diisocyanate (MDI) can also be used with various types of polymeric MDI and prepolymers of polymeric MDI.
[0038] Examples of trifunctional or higher-functional polyisocyanates include 1-methylbenzene-2,4,6-triisocyanate, 1,3,5-trimethylbenzene-2,4,6-triisocyanate, biphenyl-2,4,4'-triisocyanate, diphenylmethane-2,4,4,4'-triisocyanate, methyldiphenylmethane-4,6,4'-triisocyanate, 4,4'-dimethyldiphenylmethane-2,2',5,5'-tetraisocyanate, and triphenylmethane-4,4',4"-triisocyanate.
[0039] The isocyanate index (INDEX) is preferably 70 to 150, more preferably 80 to 130, and most preferably 90 to 120. When the isocyanate index is less than 70, the foaming moldability deteriorates. On the other hand, when the isocyanate index exceeds 150, the foam becomes too hard and brittle, resulting in poor durability. The isocyanate index is a value obtained by dividing the number of moles of isocyanate groups in the polyisocyanate by the total number of moles of active hydrogen groups such as hydroxyl groups of the polyol component or water as a foaming agent, and then multiplying this value by 100. It is calculated as [NCO equivalent of polyisocyanate / active hydrogen equivalent × 100].
[0040] Examples of the foaming agent include water, hydrocarbons, halogen compounds, and the like, and may be one of these or two or more thereof. Examples of the hydrocarbon include cyclopentane, isopentane, and n-pentane. In addition, examples of the halogen compound include dichloromethane, trichlorofluoromethane, dichlorodifluoromethane, nonafluorobutyl methyl ether, nonafluorobutyl ethyl ether, pentafluoroethyl methyl ether, and heptafluoroisopropyl methyl ether. Among them, water is particularly preferably used as the foaming agent. Water may be any of ion-exchanged water, tap water, and distilled water. When the polyol component is 100 parts by mass, the amount of water used as the foaming agent is 0.5 to 10 parts by mass, preferably 1 to 8 parts by mass, and more preferably 1.5 to 5 parts by mass.
[0041] In the polyol composition, a catalyst and an auxiliary agent are appropriately blended as other components.
[0042] The catalyst used for the polyurethane foam can be a known substance and is not particularly limited. Examples of usable catalysts include amine catalysts such as triethylamine, triethylenediamine, and tetramethylguanidine; tin catalysts such as dibutyltin dilaurate and stannous octoate; and metal catalysts (also known as organometallic catalysts) such as phenylmercuric propionate or lead octenate. The total amount of the catalyst is appropriately determined depending on the type of catalyst and is generally 0.01 to 3.0 parts by mass, preferably 0.02 to 1.5 parts by mass, and more preferably 0.05 to 1.2 parts by mass, relative to 100 parts by mass of the polyol component.
[0043] Examples of the auxiliary agent include a foam stabilizer, a cross-linking agent, a colorant, a flame retardant, an antibacterial agent, a stabilizer, and a plasticizer.
[0044] Foam stabilizers for polyurethane foam can be known substances, including silicone foam stabilizers, fluorine-containing compound foam stabilizers, and surfactants. Silicone foam stabilizers are particularly preferred. Examples of silicone foam stabilizers include those composed primarily of siloxane chains, those with a linear structure of siloxane and polyether chains, branched silicone foam stabilizers, and those with polyether chains modified into pendant-shaped structures on the siloxane chains.
[0045] Examples of the crosslinking agent include polyols such as ethylene glycol, diethylene glycol, glycerin, butane tetraol, and polyoxypropylene glycol, diethanolamine, and polyamines. These can be used alone or in combination of two or more.
[0046] Polyurethane foams include slab foamed articles and molded foamed articles, and the polyurethane foam of the present invention may be either type.
[0047] Block foam products are made by mixing and stirring a polyurethane foam composition and discharging it onto a conveyor, where it foams continuously to form the polyurethane foam. The foam is then cut into foam products of a specified size. In contrast, molded foam products are made by injecting a polyurethane foam composition into a mold and allowing it to foam. These products have an outer shape that corresponds to the inner surface of the mold.
[0048] The polyurethane foam of the present invention may be a polyurethane foam having cell membranes that have not been subjected to a film removal treatment, or may be a polyurethane foam in which a film removal treatment has been performed to remove the cell membranes.
[0049] Defilming treatment is a well-known treatment for removing the cell membrane of polyurethane foam. The defilming treatment includes a method of immersing the polyurethane foam in an alkaline solution to melt the cell membrane, or a method such as containing the polyurethane foam in a sealed container, filling the sealed container with a combustible gas such as oxygen, and then igniting it to cause it to explode, thereby destroying the cell membrane.
[0050] Example
[0051] The examples of the present invention are described in detail together with the comparative examples. Figure 1 The polyurethane foam compositions of the Examples and Comparative Examples, having the formulations shown in the table, were stirred and mixed, and foamed to produce the polyurethane foams of the Examples and Comparative Examples. Comparative Example 1 and Examples 1-3 are block foams, while Comparative Example 2 and Example 4 are molded foams. In Example 2, the polyurethane foam of Example 1 was subjected to a de-filming treatment by explosion to remove the cell membranes. Aside from the presence or absence of the cell membranes, the process was identical to that of Example 1.
[0052] <Polyol component>
[0053] Plant-derived polyol 1: Unmodified (refined) castor oil polyol, 100% plant-derived, 2.7 functional groups, 160 mgKOH / g hydroxyl value, 947 molecular weight, product name: H-30, manufactured by Ito Oil Manufacturing Co., Ltd.
[0054] Plant-derived polyol 2: 100 parts by mass of purified castor oil and 10.9 parts by mass of sebacic acid were reacted while stirring. This is a 100% plant-derived castor oil polyol with a molar ratio of purified castor oil / sebacic acid of 2 / 1. It has 3.5 functional groups, a hydroxyl value of 86 mgKOH / g, and a molecular weight of 2182.
[0055] Petroleum-derived polyol 1: Functional group number: 3, hydroxyl value: 24.1 mgKOH / g, molecular weight: 6983.4, product name: KC737, manufactured by Sanyo Chemical Industries, Ltd.
[0056] Petroleum-derived polyol 2: Functional group number: 3, hydroxyl value: 56.1 mgKOH / g, molecular weight: 3000, product name: EP505S, manufactured by Mitsui Chemicals, Inc.
[0057] Petroleum-derived polyol 3: Polyether polyol, functional group number 3, hydroxyl value 56.1 mgKOH / g, molecular weight 3000, product name: GP-3050NS, manufactured by Sanyo Chemical Industries, Ltd.
[0058] Petroleum-derived polyol 4: Functional group number 3, hydroxyl value 31 mgKOH / g, molecular weight 5429, product name: Y-7530, manufactured by Mitsui Chemicals SKC Polyurethanes Co., Ltd.
[0059] Cross-linking agent
[0060] Diethylene glycol
[0061] <Foaming agent>
[0062] ·water
[0063] <Amine Catalyst>
[0064] Amine catalyst 1: Aliphatic tertiary amine composition, product name: DABCO 33LSI, manufactured by Evonik Japan
[0065] Amine catalyst 2: Product name: 2Mabs, manufactured by Nippon Emulsifier Co., Ltd.
[0066] Foam stabilizer
[0067] Foam stabilizer 1: Silicone-based, product name: SZ1136, manufactured by Toray and Dow Corning Co., Ltd.
[0068] Foam stabilizer 2: Silicone-based, product name: L-594 Plus, manufactured by Evonik Japan
[0069] Foam stabilizer 3: silicone-based, product name: L3184J, Momentive Advanced Materials Japan Co., Ltd.
[0070] <Metal Catalyst>
[0071] Stannous octoate, product name: MRH-110, manufactured by Johoku Chemical Industry Co., Ltd.
[0072] Polyisocyanate
[0073] Polyisocyanate 1: 2,4-TDI / 2,6-TDI = 80 / 20 toluene diisocyanate, product name: Coronate T-80, manufactured by Tosoh Corporation
[0074] Polyisocyanate 2: 2,4-TDI / 2,6-TDI = 65 / 35 toluene diisocyanate, product name: Coronate T-65, manufactured by Tosoh Corporation
[0075] Polyisocyanate 3: Monomeric MDI (a mixture of 4,4'-MDI and 2,4-MDI. The ratio of 2,4-MDI is 25-50%)
[0076] The biomass content, physical properties and drying properties after washing of the polyurethane foams of each embodiment and each comparative example were measured. Figure 1 shown.
[0077] The biomass content (plant-based) refers to both a value measured by accelerator mass spectrometry (AMS method) in accordance with ASTM D6866-20 and a value obtained by calculation.
[0078] ASTM D6866 measures the carbon-14 concentration of a reference material and a reference material in the atmosphere in 1950, and defines the biomass content as the ratio of these values. However, due to the increasing concentration of carbon-14 in the atmosphere, this value is multiplied by a correction factor. In the calculations based on ASTM D6866-20, the biomass content was calculated using the 2020 atmospheric correction factor REF(pMC) = 100.0.
[0079] Biomass content was evaluated based on the AMS measurement. A value of 50% or higher was assigned a "◎" rating, a value between 24% and less than 50% was assigned a "○" rating, and a value less than 24% was assigned a "×" rating.
[0080] The calculated value is obtained by the following calculation formula: Biomass content = number of plant polyols added / (total number of added parts - gas loss) Gas loss = number of water added / 18 × 44
[0081] In the above gas loss calculation formula, "18" is the molecular weight of water, and "44" is the molecular weight of carbon dioxide.
[0082] Regarding physical properties, density (JIS K7222), 25% hardness (JIS K6400-2 6.7D method), number of cells (JIS K6400-1), air permeability (JIS K6400-7A method), tensile strength (JIS K6400-5 5), elongation (JIS K6400-5 5), tear strength (JIS K6400-5 6B), dry heat deformation (JIS K6400-4 4.5.2A method), and rebound (JIS K6400-3) were measured.
[0083] Regarding post-wash drying properties, the water absorption after washing, the water absorption after dehydration, and the water absorption after 24 hours of drying were measured using the following method. Based on the measurement results, evaluations of post-wash water absorption, post-wash dehydration, post-wash drying, and comprehensive post-wash drying properties were performed. It should be noted that molded foam products, compared to block foam products, have a surface layer that makes water difficult to drain. Therefore, separate evaluations of post-wash water absorption, post-wash dehydration, post-wash drying, and comprehensive post-wash drying properties were performed for block foam products and molded foam products.
[0084] Regarding the water absorption after washing, a vertical washing machine was used to perform the following tests on the samples of each embodiment and each comparative example: Figure 2 At the end of each wash cycle, the sample weight was measured and the water absorption rate was calculated. The water absorption rate after the third wash cycle was defined as the post-wash water absorption rate. The water absorption rate after each wash cycle was calculated using the following formula.
[0085] Water absorption rate (%) = (weight of sample after each washing process - weight of sample before washing) / (weight of sample before washing) × 100
[0086] The values of water absorption at each time are as follows Figure 3 It should be noted that "before washing" refers to the time before the first washing process begins.
[0087] Post-wash water absorption was evaluated according to the following criteria. For Comparative Example 1 and Examples 1 to 3 of the block foam product, a rating of "◎" indicated a post-wash water absorption of less than 160%, a rating of "○" indicated a post-wash water absorption of 160% to less than 200%, and a rating of "×" indicated a post-wash water absorption of 200% or greater. For Comparative Example 2 and Example 4 of the molded foam product, a rating of "◎" indicated a post-wash water absorption of less than 95%, a rating of "○" indicated a post-wash water absorption of 95% to less than 100%, and a rating of "×" indicated a post-wash water absorption of 100% or greater.
[0088] Regarding the water absorption rate after dehydration, after the third washing process is completed, Figure 2For the first and second dehydration cycles shown, at the end of each dehydration cycle, the sample weight was measured and the water absorption was calculated. The water absorption after the second dehydration cycle was defined as the post-dehydration water absorption. The water absorption after each dehydration cycle was calculated using the following formula.
[0089] Water absorption rate (%) = (weight of sample after each dehydration process - weight of sample before washing) / (weight of sample before washing) × 100
[0090] The water absorption rate after each dehydration process is as follows Figure 3 shown.
[0091] Post-wash dehydration performance was evaluated according to the following criteria. For Comparative Example 1 and Examples 1 to 3 of the block foam product, a rating of "◎" indicates a water absorption rate of less than 120% after dehydration; a rating of "○" indicates a water absorption rate of 120% to less than 185% after dehydration; and a rating of "×" indicates a water absorption rate of 185% or greater after dehydration. For Comparative Example 2 and Example 4 of the molded foam product, a rating of "◎" indicates a water absorption rate of less than 90% after dehydration; a rating of "○" indicates a water absorption rate of 90% to less than 95% after dehydration; and a rating of "×" indicates a water absorption rate of 95% or greater after dehydration.
[0092] For the water absorption after 24 hours of drying, the sample was left at room temperature (20-28°C is considered room temperature) for 24 hours after the second dehydration process. The water absorption was then calculated based on the sample weight. The water absorption after 24 hours of drying was calculated using the following formula.
[0093] Water absorption after drying for 24 hours (%) = (weight of sample after standing for 24 hours - weight of sample before washing) / (weight of sample before washing) × 100
[0094] The water absorption value after drying for 24 hours is as follows Figure 3 shown.
[0095] Post-wash drying properties were evaluated according to the following criteria. For Comparative Example 1 and Examples 1 to 3 of the block foam product, a "◎" rating was assigned when the water absorption was less than 1% after 24 hours of drying; a "○" rating was assigned when the water absorption was 1 to less than 3% after 24 hours of drying; and a "×" rating was assigned when the water absorption was 3% or greater after 24 hours of drying. For Comparative Example 2 and Example 4 of the molded foam product, a "◎" rating was assigned when the water absorption was less than 5% after 24 hours of drying; a "○" rating was assigned when the water absorption was 5 to less than 10% after 24 hours of drying; and a "×" rating was assigned when the water absorption was 10% or greater after 24 hours of drying.
[0096] Regarding the comprehensive evaluation of washing and drying properties, if the water absorption evaluation after washing, the water dehydration evaluation after washing, and the drying properties after washing are only "◎" or consist only of "◎" and "○", the comprehensive evaluation of washing and drying properties is set to "◎". If the water absorption evaluation after washing, the water dehydration evaluation after washing, and the drying properties after washing are all "○", the comprehensive evaluation of washing and drying properties is set to "○". If even one of the water absorption evaluation after washing, the water dehydration evaluation after washing, and the drying properties after washing is "×", the comprehensive evaluation of washing and drying properties is also set to "×".
[0097] <Results of Comparative Example 1 and Examples 1 to 3 of Block Foam Products>
[0098] Comparative Example 1
[0099] Comparative Example 1 is an example in which the polyol component is 100 parts by mass of the petroleum-derived polyol 3 and 0 parts by mass of the vegetable oil-derived polyol.
[0100] In Comparative Example 1, the biomass content based on the AMS method was 1%, the biomass content evaluation was "×", the calculated biomass content was 0%, the water absorption after washing was 248.4%, the water absorption after washing was evaluated as "×", the water absorption after dehydration was 193.3%, the dehydration evaluation after washing was "×", the water absorption after drying for 24 hours was 3.95%, the drying evaluation after washing was "×", and the overall drying evaluation after washing was "×".
[0101] Example 1
[0102] Example 1 is an example in which the polyol component composition is 60 parts by mass of the plant-derived polyol 1, 20 parts by mass of the vegetable oil-derived polyol 2, and 20.45 parts by mass of the petroleum-derived polyol 3.
[0103] In Example 1, the biomass content based on the AMS method was 58%, and the biomass content evaluation was "◎". The calculated biomass content was 53%, the water absorption after washing was 169.9%, and the water absorption after washing was evaluated as "○". The water absorption after dehydration was 137.0%, and the dehydration after washing was evaluated as "○". The water absorption after drying for 24 hours was 0.06%, and the drying property after washing was evaluated as "◎". Any of the water absorption after washing, the water absorption after dehydration, and the water absorption after drying for 24 hours was less than that of Comparative Example 1, and the comprehensive drying property evaluation after washing was "◎".
[0104] Example 2
[0105] Example 2 is an example in which a polyurethane foam is subjected to a film removal treatment and a cell film is removed. The polyurethane foam is formed from a polyol composition having the same formulation as that of Example 1.
[0106] Example 2 showed the same physical properties and biomass content as Example 1 having the same polyol composition formulation. The biomass content based on the AMS method was 57%, the biomass content evaluation was "⊚", and the calculated biomass content was 53%.
[0107] In Example 2, the water absorption after washing was 136.0%, resulting in a "◎" rating for water absorption after washing; the water absorption after dehydration was 107.2%, resulting in a "◎" rating for dehydration after washing; and the water absorption after 24 hours of drying was 0.06%, resulting in a "◎" rating for dryness after washing. Each of the water absorption after washing, the water absorption after dehydration, and the water absorption after 24 hours of drying was lower than that of Comparative Example 1, resulting in a "◎" rating for overall dryness after washing. It should be noted that by removing the cell membranes of the polyurethane foam, the water absorption after washing and the water absorption after dehydration were lower than those of Example 1, indicating excellent dryness.
[0108] Example 3
[0109] Example 3 is an example in which the polyol component composition is 37 parts by mass of the plant-derived polyol 1 and 63 parts by mass of the petroleum-derived polyol 4.
[0110] In Example 3, the biomass content based on the AMS method was 28%, and the biomass content evaluation was "○". The calculated biomass content was 26%, the water absorption after washing was 197.1%, and the water absorption after washing was evaluated as "○". The water absorption after dehydration was 184.7%, and the dehydration after washing was evaluated as "○". The water absorption after drying for 24 hours was 1.77%, and the drying property after washing was evaluated as "○". Any of the water absorption after washing, the water absorption after dehydration, and the water absorption after drying for 24 hours was less than that of Comparative Example 1, and the comprehensive drying property evaluation after washing was "○".
[0111] <Results of Comparative Example 2 and Example 4 of Molded Foam Products>
[0112] Comparative Example 2
[0113] Comparative Example 2 is an example in which the polyol component composition includes 70 parts by mass of petroleum-derived polyol 1, 10 parts by mass of petroleum-derived polyol 2, and 20 parts by mass of petroleum-derived polyol 3, and 0 parts by mass of vegetable oil-derived polyol.
[0114] In Comparative Example 2, the calculated biomass content was 0%, the water absorption after washing was 115.6%, the water absorption after washing was evaluated as "×", the water absorption after dehydration was 96.4%, the dehydration after washing was evaluated as "◎", the water absorption after 24 hours of drying was 13.7%, the drying after washing was evaluated as "×", and the comprehensive drying after washing evaluation was "×".
[0115] Example 4
[0116] Example 4 is an example in which the polyol component composition is 22 parts by mass of plant-derived polyol 1, 17 parts by mass of vegetable oil-derived polyol 2, 51 parts by mass of petroleum-derived polyol 1, and 10 parts by mass of petroleum-derived polyol 2.
[0117] In Example 4, the biomass content based on the AMS method was 27%, and the biomass content was evaluated as "○". The calculated biomass content was 23%, the water absorption after washing was 94.0%, and the water absorption after washing was evaluated as "◎". The water absorption after dehydration was 87.5%, and the dehydration after washing was evaluated as "◎". The water absorption after drying for 24 hours was 4.1%, and the drying property after washing was evaluated as "◎". Any of the water absorption after washing, the water absorption after dehydration, and the water absorption after drying for 24 hours was less than that of Comparative Example 2, and the comprehensive evaluation of drying property after washing was "◎".
[0118] Thus, the polyurethane foam of the present invention has good drying properties after washing.
[0119] It should be noted that the present invention is not limited to the embodiments and can be modified without departing from the scope of the invention.
[0120] Industrial applicability
[0121] The polyurethane foam of the present invention has good drying properties after washing and can be used for articles to be washed, such as bedding such as mattresses and pillows, furniture such as seat cushions, and clothing such as bra pads for underwear.
Claims
1. An article, wherein The article is any one of bedding, furniture or clothing, Regarding the polyurethane foam, the biomass content measured according to ASTM D6866-20 is 57% or more, The number of units based on JIS K6400-1 is 30 to 38 / 25mm. The 25% hardness based on JIS K6400-2 6.7D method is 70 to 180N.
2. An article, wherein The article is any one of bedding, furniture or clothing, Regarding the polyurethane foam, the biomass content measured according to ASTM D6866-20 is 24% or more, The number of units based on JIS K6400-1 is 30 to 38 / 25mm. Density based on JIS K7222: 26.2 to 31.1 kg / m 3 , The 25% hardness based on JIS K6400-2 6.7D method is 70 to 180N. Air permeability based on JIS K6400-7A method: 28.8 to 249cc 3 / cm 2 ·s, The elongation based on JIS K6400-5 5 is 133 to 194%, The tear strength based on JIS K6400-5 6B is 5.1 to 7.9 N / cm.
3. The article according to claim 1 or 2, wherein The raw materials of the polyurethane foam contain a reaction product of castor oil and sebacic acid.
4. The article according to claim 1 or 2, wherein: The article is a breast pad for underwear.
5. The article according to claim 1 or 2, characterized in that The water absorption rate after washing, the water absorption rate after dehydration, and the water absorption rate after drying for 24 hours of the polyurethane foam were measured using the following methods: In the case where the polyurethane foam is a block foam, the water absorption after washing is less than 200%, the water absorption after dehydration is less than 185%, and the water absorption after drying for 24 hours is less than 3%. In the case where the polyurethane foam is a molded foam product, the water absorption after washing is less than 100%, the water absorption after dehydration is less than 95%, and the water absorption after drying for 24 hours is less than 10%. The method for measuring the water absorption rate after washing is to use a vertical washing machine to sequentially perform a first washing procedure, a second washing procedure, and a third washing procedure on the polyurethane foam sample, measure the weight of the sample at the end of each washing procedure and calculate the water absorption rate, and set the value of the water absorption rate after the end of the third washing procedure as the water absorption rate after washing. Water absorption after washing (%) = (weight of sample after each washing procedure - weight of sample before washing) / (weight of sample before washing) × 100, The method for measuring the water absorption rate after dehydration is as follows: after the third washing program is completed, the first dehydration program and the second dehydration program are performed in sequence, at the end of each dehydration program, the weight of the sample is measured and the water absorption rate is calculated, and the water absorption rate after the second dehydration program is set as the water absorption rate after dehydration. Water absorption rate after dehydration (%) = (weight of sample after each dehydration process - weight of sample before washing) / (weight of sample before washing) × 100, The water absorption rate after drying for 24 hours is calculated by placing the sample at room temperature for 24 hours after the second dehydration process, and then calculating the water absorption rate after drying for 24 hours based on the weight of the sample, wherein 20-28°C is referred to as room temperature. Water absorption after drying for 24 hours (%) = (weight of sample after standing for 24 hours - weight of sample before washing) / (weight of sample before washing) × 100, In the first washing program, the washing time is 11 minutes, the rinsing time is 26 minutes, and the dehydration time is 10 minutes. In the second washing program, the rinsing time is 26 minutes and the dehydration time is 10 minutes. In the third washing program, the rinsing time is 26 minutes and the dehydration time is 10 minutes. In the first dehydration program, the dehydration time is 10 minutes. In the second dehydration program, the dehydration time is 10 minutes.
Citation Information
Patent Citations
Washing sponge
JP2005270146A
Cleaning sponge
JP2019017948A
Polyurethane foam, clothing material, brassiere pad, brassiere cup, and method for producing polyurethane foam
JP2019203061A